Research plays engagement to cope the females children aggression at primary school - Lai Xuan Thuy, Nguyen Minh Xuan Huong (Innovative Journal of Medical and Health Sciences, 2020)
Aggressive behaviors among young people represent a common concern and many females and adolescent girls report having been victimized or bullied. Cost effective strategies are needed to deal with this problem. Current research has investigated the effect of fighting on cognitive aggression in elementary school girls. Using a vertical design, 63 fourth- and fifth-graders (31 fourth and 32 grade 5, average age = 9.6 ± 0.5 years) participated in a controlled controlled game of On school 2 days a week for 4 consecutive weeks, program replication was adopted in a previous study with 13-year-old junior high school students. Participants filled out a short version of 12 questions of the three-time Invasion Question: the basic stage (A0 and A1) and after the battle intervention (A2). An RM-ANOVA showed significance in the topic difference between the three assessments (F = 2.91, P = 0.003). At the verbal abuse level, A1’s anger and hostility significantly decreased, while in the post-intervention phase, only physical aggression was significantly lower than A1 (A1 = 5, 45 ± 2.47; A2 = 5.04 ± 2.41; F = 5.22, p = 0.005). The results provide some preliminary insights into the role that fighting can be part of a physical education program to cope with aggressive and antisocial behaviors of children, confirming conclusions. encouraging of previous research in adolescents. Key words: aggressive behaviours, female children, peer-aggression, physical education, play engagement.